High Resolution Interferometric Infrared Spectroscopy of CO2 and CH4 Vapour at Low Temperatures Near 10 K: Collisional Cooling in Supersonic Jets and Nuclear Spin Symmetry Conservation - Hans-Rolf Dübal; Martin Quack; Ulrich Schmitt (CHIMIA)
Infrared absorption spectra of gaseous CO2 near 2350 cm-1 and CH4 near 3030 cm-1 were obtained with apodized resolutions up to 0.006 cm-1 in a supersonic jet-FTIR spectrometer system. Effective rotational temperatures near 10 K were obtained. The evidence for nuclear spin symmetry conservation in the supersonic jet cooling of methane is discussed.